HARMONY OF THE INDIVIDUAL’S SPIRITUAL BEING AND VALUES IN THE HERITAGE OF EASTERN THINKERS (Eureka Journal of Humanities and Social Research, 2026)
This article explores the harmony between the spiritual being of the individual and value systems in the intellectual heritage of Eastern thinkers. The study analyzes the socio-philosophical views of classical scholars regarding moral perfection, ethical norms, and the formation of a spiritually mature personality. Particular attention is paid to the ideas of prominent Eastern philosophers who emphasized the interdependence of knowledge, morality, and social responsibility in shaping human existence. The paper also examines the role of cultural and historical heritage in preserving value continuity and fostering spiritual development in contemporary society. Based on the analysis, the article identifies key conceptual approaches to understanding the unity of spiritual being and values within the framework of Eastern philosophical thought.
Keywords: Eastern philosophy, spiritual being, values, moral development, harmony, personality formation, cultural heritage, ethical norms, socio-philosophical analysis.